Selective modification of electrical insulator material by ion micro beam for the fabrication of circuit elements. Issue 3 (3rd March 2020) - Cutroneo, M.; Havranek, V.; Mackova, A.; Malinsky, P.; Torrisi, A.; Silipigni, L.; Sofer, Z.; Torrisi, L.
Abstract : Two well-established electrical insulators, graphene oxide and poly(methylmethacrylate) (PMMA) have been selectively exposed to controlled energy and fluence of ions. Ion micro beam has been proposed for processing of both graphene-based material and polymeric foils for tailoring of their properties. In a single step, the mask-less production of pattern on graphene-oxide and poly(methylmethacrylate) was realized at the Tandetron Laboratory of the Nuclear Physics Institute (Czech Republic) using a stream of 2.2 MeV alpha particles. Elements of a circuit were written on GO and poly(methylmethacrylate) in a controlled way using a software written in LabVIEW code. The induced deoxygenation, and dehydrogenation change the compositional, structural and electrical properties in the exposed samples. The accuracy of the method has been investigated by Rutherford backscattering spectrometry, elastic recoil detection analysis, Raman microscopy and the electrical standard two points method.